2018
DOI: 10.1002/cctc.201801423
|View full text |Cite
|
Sign up to set email alerts
|

Facet Sensitivity of Capping Ligand‐Free Ag Crystals in CO2 Electrochemical Reduction to CO

Abstract: Silver‐based electrocatalysts are active in catalyzing electrochemical reduction of CO2 to CO. We herein report synthesis of capping ligand‐free Ag cubes and octahedra by morphology‐preserved CO reduction from corresponding Ag2O counterparts and their performance in electrochemical reduction of CO2. Ag cubes are much more active than Ag octahedra and exhibit a stable CO formation rate as high as 142.4 mmolCO gcat−1 h−1 at −0.95 V (vs. RHE). Ag films transiently formed on Ag2O crystals during CO2 electroreducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 30 publications
(18 reference statements)
1
18
0
1
Order By: Relevance
“…To be more specific, Ag (110) is demonstrated to exhibit a j CO which is five times larger than that of Ag(111) and Ag(100) at an applied potential of −1.44 V . Similar findings were also reported with capped ligand‐free Ag crystals (c‐Ag), where c‐Ag catalyst with exposed (110) facet demonstrated a much lower charge transfer resistance compared to other control catalysts that were exposing only (111) facets, respectively . In addition to Ag(110) facets, it was also discovered that optimal edge‐to‐corner ratio can improve the catalytic selectivity of CO 2 RR to CO as the edge sites can lower the energy barrier for the rate determining *COOH radicals, as indicated by DFT calculations .…”
Section: Active Sites In Metal‐based Catalystssupporting
confidence: 63%
“…To be more specific, Ag (110) is demonstrated to exhibit a j CO which is five times larger than that of Ag(111) and Ag(100) at an applied potential of −1.44 V . Similar findings were also reported with capped ligand‐free Ag crystals (c‐Ag), where c‐Ag catalyst with exposed (110) facet demonstrated a much lower charge transfer resistance compared to other control catalysts that were exposing only (111) facets, respectively . In addition to Ag(110) facets, it was also discovered that optimal edge‐to‐corner ratio can improve the catalytic selectivity of CO 2 RR to CO as the edge sites can lower the energy barrier for the rate determining *COOH radicals, as indicated by DFT calculations .…”
Section: Active Sites In Metal‐based Catalystssupporting
confidence: 63%
“…It was also reported that structure, morphology, size, and composition of the catalyst can lead to adsorption and decoupling site preferences of different adsorbates of C bound on the surface and further result in the breaking of the linear scaling relationships and tuning of the adsorption strength, eventually exerting a dramatic influence on the ECR performance . Indeed, in addition to polycrystalline and single‐crystalline Ag, some new A types have been developed and characterized recently, such as nanostructured Ag with different sizes, supported Ag catalysts with different substrates including C, TiO 2 , Al 2 O 3 , dopant‐aided Ag, oxide‐derived Ag, and surface‐modified Ag …”
Section: Advances In Ag‐based Co2‐to‐co Electrocatalystsmentioning
confidence: 99%
“…Clearly, tuning of nanocrystalline Ag electrocatalysts in terms of their geometrical parameters such as size and shape plays a significant role in the improvement of catalytic performance for selective ECR to CO. Indeed, the impact of both particle size and nanomorphology of Ag electrocatalysts has been widely reported for selective ECR to CO in literature …”
Section: Advances In Ag‐based Co2‐to‐co Electrocatalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al. compared cubic and octahedral Ag NPs, representing (100) and (111) surfaces, respectively, and the higher CO current on the cubic NPs confirmed strong facet dependency of Ag …”
Section: Designer Metal Nanoparticles For Electrocatalytic Co2rrmentioning
confidence: 99%